Music technology in therapeutic and health settings - Magee, Wendy (London Jessica Kingsley Publishers, 2014)
"There is a rapidly emerging and developing area of music therapy practice that uses electronic music technologies in a range of therapeutic and clinical settings to help clients with complex needs. This edited volume explains cutting edge technologies and how to apply these tools in practice. With contributions from leading experts in the field, the book takes the reader through the equipment that is available including computer-based software; electronic devices which produce musical sounds with minimal movement or skill; assistive devices such as switches and sensors; and recording and listening equipment. Clinical case studies are then offered that show these technologies being used successfully with a broad range of child and adult populations, including those with visual impairments, autism spectrum disorders, medical needs, physical challenges, and mental health issues, and within a variety of settings, including a neonatal intensive care unit, schools, hospital environments, and palliative care settings. The final section looks toward the future and examines philosophical and theoretical perspectives on the use of technology and its relationship to aesthetics, gender and identity. This book will be a key resource for all music therapists, special needs educators, and professionals from the field of assistive technology, as well as allied health professionals such as occupational therapists and speech and language therapists." -- Publisher's description.
Music technology in therapeutic contexts with adults. Using GarageBand music software with adults with acquired brain injury at Headway East London : identity, communication, and executive function Alex Street. Playing the band : the story of The Headbangers, a performance ensemble for young people and young adults using assistive devices Jon Adams and Marcia Lajoie. The birth of a therapeutic recording studio : addressing the needs of the Hip-Hop generation on an adult inpatient psychiatric unit Nir Sadnovik. Creative adaptations of music technology in adult cancer care Lorrie Kubicek. GarageBand as a digital co-facilitator : creating and capturing moments with adults and elderly people with chronic health conditions Ariel Weissberger -- Theory, research, and practice : future directions for music technology in therapeutic contexts. Therapeutic songwriting with clients in an e-health environment Felicity Baker and Robert E. Krout. Gender-technology relations in the training and practice of music technology in therapeutic settings Wendy L. Magee and Davis Wimberly. Music technology and identity in therapeutic contexts Karen Burland and Wendy L. Magee. $t Music aesthetics, music technology, and music therapy Joseph Nagler. Models for roles and collaborations when using music technology in music therapy Wendy L. Magee.
Includes bibliographical references (pages 385-386) and index.
Keywords: Music therapy; Music therapy -- Technological innovations; Music and technology